2019
DOI: 10.1111/rda.13558
|View full text |Cite
|
Sign up to set email alerts
|

An approach to study the local embryo effect on gene expression in the bovine oviduct epithelium in vivo

Abstract: This study aimed to examine the local embryo effect on the transcriptomic response of the epithelial cells of the oviduct in vivo. Fifteen heifers were synchronized and artificially inseminated to a standing heat. All heifers were slaughtered on Day 2.5 after oestrus. The oviducts from 13 animals were isolated, trimmed free of tissue and divided between ampulla/isthmus. The ipsilateral isthmus was divided into smaller sections (2 cm). Each section was sequentially flushed until the embryo was located (4/13) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We identify here also original genes related to stromal cell differentiation and cell migration such as CDH11, PRELP, THY1 (the latter encoding a stem cell marker) [ 66 ], GJA1 [ 67 ], OSR2 [ 68 ], P4HA3. PRLEP gene expression has been reported to be regulated by the embryo in the bovine oviduct [ 69 ]. Contrary to the porcine endometrium where its expression was reported to be located in epithelial cells [[ 70 ], NTRK2 was mainly expressed here in stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…We identify here also original genes related to stromal cell differentiation and cell migration such as CDH11, PRELP, THY1 (the latter encoding a stem cell marker) [ 66 ], GJA1 [ 67 ], OSR2 [ 68 ], P4HA3. PRLEP gene expression has been reported to be regulated by the embryo in the bovine oviduct [ 69 ]. Contrary to the porcine endometrium where its expression was reported to be located in epithelial cells [[ 70 ], NTRK2 was mainly expressed here in stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, the endoscopic transfer of 50 in vitro produced bovine zygotes on day 1.5 post-estrus in heifers led to significant changes in the gene expression of the isthmus on day 3 post-estrus [82]. In order to avoid a dilution of an embryonic effect in a physiological situation, Rodriguez-Alonso et al [83] focused on 2 cm oviduct sections in which the cattle embryo was retrieved on day 2.5 after insemination and made comparisons on candidate gene expression with adjacent sections in the same oviduct or with the same section in the contralateral oviduct. However, no site-specific effect of the cattle embryo could be evidenced with this method.…”
Section: Pregnancy and Embryomentioning
confidence: 92%
“…Different studies have demonstrated changes in gene expression patterns of bovine OECs co-cultured with embryos (11,12). In vivo, despite no differences in OECs gene expression were found using microarray analysis in the presence of a single embryo in artificially inseminated heifers compared to cyclic heifers by Maillo et al (13) or using target genes analysis by Rodríguez-Alonso et al (14), the same group identified differentially expressed genes by RNA-seq when multiples embryos were transferred (13). In the oviductal fluid, different proteins were described indicating that the fluid composition could be influenced by the presence of gametes (15).…”
Section: Introductionmentioning
confidence: 98%